Relationship between Gastrointestinal Problems and Quality of Life of Rural Population of a Tertiary Care Hospital Lahore - Abbas, Nosheen; Kaynat, Sidra; Sharjeel Bin Munir; Bashir, Fouzia; Naeem, Abi; Raza, Ahmad; Raza, Hasnain Ahmad (Indus Journal of Bioscience Research, 2025)
Background: Gastrointestinal problems are prevalent globally and significantly impacts the overall well-being and quality of life. Gastritis, peptic ulcers, irritable bowel syndrome (IBS), constipation, and acid reflux influence the physical and emotional well-being of patients. Methodology: This descriptive cross-sectional study at Jinnah Hospital, Lahore, included 300 rural patients diagnosed with gastrointestinal problems, excluding those with psychological disorders. Data were collected using the WHO Quality of Life questionnaire over two months, with ethical approval and informed consent obtained. Statistical analysis was conducted using SPSS 25, employing descriptive statistics and Pearson correlation to assess the relationship between GI symptoms and quality of life. A p-value <0.05 was considered statistically significant. Results: The study indicated that majority of participants were aged 46–60 years (35%) and female (53.3%). Nearly half were illiterate (46.7%), most were married (66.7%), and a majority were unemployed (73.3%). Regarding quality of life (QoL), 45% reported good, 40% moderate, 8.3% poor, and 6.7% very good QoL. Analysis revealed that participants experiencing gastrointestinal symptoms such as abdominal pain, bloating, indigestion, nausea, vomiting, diarrhea, and constipation were significantly more likely to report lower QoL, falling into the poor or moderate categories. All these associations were statistically significant (p < 0.05), underscoring a strong negative impact of GI problems on quality of life in this rural population. Conclusion: The study found that gastrointestinal symptoms were significantly associated with lower quality of life among rural patients, with those affected more likely to report poor to moderate QoL. Conversely, participants without GI symptoms generally reported better quality of life, highlighting the substantial negative impact of GI disorders in this population.